2020
DOI: 10.1016/j.psj.2020.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of extended-spectrum β-lactamases-producing Escherichia coli from broiler chickens at different day-age

Abstract: Commensal Escherichia coli from the poultries have been considered as reservoirs of extended-spectrum β-lactamases ( ESBL )-encoding genes. Between May 2018 and March 2019, a total of 340 E. coli isolates were obtained from apparently healthy broiler chickens from 20 to 40 D old, distributed in 17 small-scale commercial farms. Finally, 45 isolates (8 from 20-day-old broiler chickens, 14 from 30-day-old ones, and 23 from 40-day-old ones) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In the present study, ST23 was reported in one isolate which harbored mcr -1. The ST23 was previously reported by China which harbored ESBL-resistant genes including bla CTX-M , bla TEM , and bla SHV [ 45 ]. Generally, it is fact that mcr genes have been identified on diverse STs in E. coli isolated from human, animal, and food samples suggesting the dissemination of genes successfully through the mobile genetic element (MGE) and plasmid rather than dissemination of specific clones of E. coli [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ST23 was reported in one isolate which harbored mcr -1. The ST23 was previously reported by China which harbored ESBL-resistant genes including bla CTX-M , bla TEM , and bla SHV [ 45 ]. Generally, it is fact that mcr genes have been identified on diverse STs in E. coli isolated from human, animal, and food samples suggesting the dissemination of genes successfully through the mobile genetic element (MGE) and plasmid rather than dissemination of specific clones of E. coli [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the four CTX-M-65 producers co-harbored qnrS and aac(6′)-Ib-cr [ 72 ]. Studies in China in Enterobacteriaceae ESBL producers identified strains co-harboring two and three PMQR-encoding mechanisms simultaneously [ 76 , 101 ]. Although uncommon, in Europe, some Enterobacteriaceae strains from animals, food, and the environment co-harboring two PMQR encoding genes, were found, although not mentioning they were ESBL producers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…bla CTX – M – 65 gene is widely found in E. coli isolated from food-producing animals and no sequence type related to the widespread popularity of CTX-M-65-type ESBL has been found. Previous study showed that E. coli ST410 encoding bla CTX – M – 65 had been obtained from healthy broiler chickens ( Liu et al, 2020 ). It is very likely that poultry will be sources of bla CTX – M – 65 and transfer this resistant gene to human via food supply chain.…”
Section: Discussionmentioning
confidence: 99%